Analisis Risiko Dan Identifikasi Potensi Bahaya Pada Area Penerimaan Barang Di Warehouse - Doifurrahman, Abdan; Harlan, Fandy Bestario (Publika Bersama Nusantara, 2025)
The research conducted aims to identify hazard risks in receiving activities at the PT XYZ Warehouse. Data collection was carried out through field observations and interviews. Implemented using the Failure Mode and Effect Analysis (FMEA) method in analyzing potential risks and hazards to obtain a Risk Priority Number (RPN) value as a risk control priority. The results of the study obtained 10 potential hazards with 11 risks that can cause work accidents. The highest RPN was obtained in the process of physical inspection of work goods with the potential hazard of using cutting tools. The RPN value obtained was 32. Potential hazards can be avoided by controlling the use of personal protective equipment (PPE), monitoring, and increasing self-awareness that occupational safety and health are important.